1994
DOI: 10.1097/00000658-199402000-00006
|View full text |Cite
|
Sign up to set email alerts
|

A Laparoscopic Intraperitoneal Onlay Mesh Technique for the Repair of an Indirect Inguinal Hernia

Abstract: ObjectiveThis study was done (1) to determine whether congenital indirect inguinal hernias in male pigs could be repaired by placing a polypropylene mesh prosthesis over the defect intra-abdominally, (2) to measure the incidence of adhesions between intra-abdominal viscera and the prosthesis with and without the adhesion barrier oxidized regenerated cellulose, (3) to determine the incidence of other complications, and (4) to assess the effect on fertility. Summary Background DataSeveral techniques for laparosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
6

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(52 citation statements)
references
References 9 publications
(5 reference statements)
2
44
0
6
Order By: Relevance
“…However microscopic analysis of the two cases demonstrated vascular neoformation, an inflammatory reaction, collagen deposition without fibrosis and microcyst formation, but with partial incorporation of the biomembrane. This showed that the reduced thickness of the porous biomembrane was of some benefit, in agreement with literature reports 10,11,17,19 that demonstrated the need for pores in the prosthesis for intermingled fibroblast proliferation to occur with consequent incorporation. These facts suggest that a less thick biomemnbrane appears to be a factor influencing incorporation into adjacent tissues.…”
Section: Collagen Microcystsssupporting
confidence: 90%
See 1 more Smart Citation
“…However microscopic analysis of the two cases demonstrated vascular neoformation, an inflammatory reaction, collagen deposition without fibrosis and microcyst formation, but with partial incorporation of the biomembrane. This showed that the reduced thickness of the porous biomembrane was of some benefit, in agreement with literature reports 10,11,17,19 that demonstrated the need for pores in the prosthesis for intermingled fibroblast proliferation to occur with consequent incorporation. These facts suggest that a less thick biomemnbrane appears to be a factor influencing incorporation into adjacent tissues.…”
Section: Collagen Microcystsssupporting
confidence: 90%
“…In a further attempt to improve the performance of the latex biomembrane, a new modification was introduced in its structure, rendering it porous, based on the results reported by Stoppa et al 7 , Fitzgibbons et al 19 , Dion and Morin 10 , McKernan and Laws 17 . The results obtained with the latex biomembrane with 1-mm thick polyamide in group 3 were similar to thouse obtained for the group implanted with latex with impermeable polyamide, demonstrating that the presence of pores in the biomembrane with thick porous polyamide did not contribute to improving the results regarding incorporation.…”
Section: Collagen Microcystssmentioning
confidence: 99%
“…[1][2][3] The current methods of laparoscopic hernia repair involve the application of a preperitoneal prosthetic mesh over the hernia spaces, creating a tension-free repair. 4,5 The mesh is fixed in place using metal staples to prevent graft displacement, with consequent hernia recurrence. 6 Laparoscopic herniorrhaphy is not devoid of complications.…”
Section: Resultsmentioning
confidence: 99%
“…Quince años después es un procedimiento consolidado y con tecnología especializada. Presenta como ventajas un menor dolor y disconfort postoperatorio, una recuperación más rápida de la actividad física y laboral, la posibilidad de reparar hernias recidivadas en territorio virgen y bilaterales por la misma incisión, laparoscopia diagnóstica simultánea, y mejor resultado estético [1][2][3][4][5] . Más aún, debido a que trata la hernia en el lugar donde se produce, permite realizar una ligadura alta del saco peritoneal y colocar sin tensión una malla en el espacio preperitoneal.…”
Section: Introductionunclassified